Castil-Blaze troubadour - Séverine Féron (Lengas)
François-Henri-Joseph Blaze alias Castil-Blaze (1784-1857) is a very active author and composer in the French musical life. Born in the Comtat-Venaissin region, his bilingualism is the foundation of his distant and critical view of the musical practices of his time. A forerunner of the Félibrige, he never ceased to claim his cultural singularity by writing, collecting and publishing Provençal repertoire, both poetic and musical. While Castil-Blaze's Parisian production and career are relatively well known, its Provençal corpus and roots have received very little attention. The aim here is to identify the first outlines of the Provençal work and biography of Castil-Blaze.